Аналіз завадостійкості способу передачі інформації у запитальних радіолокаційних системах спостереження - Шевцов, І. О.; Обод, І. І. (ХНУРЕ, 2023)
In the presented work, the noise immunity of the existing and proposed method for transmitting flight information from an airborne object through the channel of interrogation radar systems for monitoring airspace is assessed, taking into account the impact of intentional chaotic (correlated and uncorrelated) impulse noise and fluctuation noise.
Keywords: об'єкт повітрянний; передавання польотної інформації